Characterization of lesion formation in marmosets following inhalational challenge with different strains of Burkholderia pseudomallei. Issue 6 (19th January 2016) - Nelson, Michelle; Nunez, Alejandro; Ngugi, Sarah A.; Sinclair, Adam; Atkins, Timothy P.
Summary: The marmoset model of melioidosis was used to explore whether there was any difference in the disease presentation and/or the lesion formation following inhalational challenge with one of four strains of Burkholderia pseudomallei (K96243, 1026b, HBPUB10303a and HBPUB10134a). Marmosets were challenged with a range of bacterial doses and bacterial load, histological and physiological features were determined temporally following lethal disease. Melioidosis presented as an acute, febrile disease with bacteraemia, bacterial dissemination, necrotizing hepatitis, splenitis and pneumonia which was independent of the challenge strain. Generally, there were no major differences in the manifestation of melioidosis following challenge by the different strains of B. pseudomallei ; however, there were some differences in the time to death and the severity of the pathological features. The pathological features observed in the liver and spleen of animals challenged with B. pseudomallei strain 1026b were statistically less severe ( P < 0.05) and less frequent. However, more severe foci of disease were evident in the lungs of animals challenged with strain 1026b. In all cases, the lesions developed from small areas of bacteria‐infected macrophages surrounded by non‐infected neutrophils into large lesions with both immune cell types infected. The marmoset model was a useful tool enabling the distinction of subtle difference in the pathological response to B. pseudomallei .